1990
DOI: 10.1002/ijc.2910460333
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and anti‐tumor resistance. V. Production of a cytostatic factor following cooperation of elicited polymorphonuclear leukocytes and macrophages

Abstract: When Lewis tumor cells (3LL) included in a gel of polyacrylamide microbeads are injected into mice and recovered 1 day later, incorporation of 125I-UdR is strongly reduced. In contrast, no reduction is observed in irradiated mice. The cytostatic effect is non-existent in 6 hr-old granuloma (granulocytes 90%, macrophages 10%), but is maximal in 48 hr-old granuloma (granulocytes 50%, macrophages 50%). When 6 hr-old granuloma cells (which are not cytostatic) are incubated with bone-marrow-derived macrophages (BMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Later, Takasugi et al showed that peripheral blood PMN possessed nonspecific cytotoxicity against various cultured human tumor lines,17 and Clark et al reported that peroxidase systems present in inflammatory cells,18 and especially the PMN,19 were cytotoxic for mouse lymphoma cells. Over the following years, a large number of reports showed that PMN had cytotoxic and/or cytostatic effects on cancer cells in vitro 20–95. Weiss and Slivka showed that the ability of PMN to destroy human T lymphoblasts was at least the same as that of monocytes,35 and in mice, PMN were found more cytotoxic to several tumors than were macrophages 53.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Later, Takasugi et al showed that peripheral blood PMN possessed nonspecific cytotoxicity against various cultured human tumor lines,17 and Clark et al reported that peroxidase systems present in inflammatory cells,18 and especially the PMN,19 were cytotoxic for mouse lymphoma cells. Over the following years, a large number of reports showed that PMN had cytotoxic and/or cytostatic effects on cancer cells in vitro 20–95. Weiss and Slivka showed that the ability of PMN to destroy human T lymphoblasts was at least the same as that of monocytes,35 and in mice, PMN were found more cytotoxic to several tumors than were macrophages 53.…”
Section: Historical Overviewmentioning
confidence: 99%
“…This is a general phenomenon since in lines of mice selected for high or low antibody responsiveness the normal process of multiplication and differentiation of lymphoid tissue was modified with a consequent effect on lymphoma frequency (Covelli et al, 1989). The defense mechanisms developed by the organism against tumorigenesis may be mediated by immunological responses endowed with specificity and memory (Burke and Balkwill, 1996; Klein and Boon, 1993) or non‐specific reactions based essentially in the different forms of inflammation (Hevin et al, 1990; DiGiovanni et al, 1992; Moore et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A eficácia terapêutica de citocinas pró-inflamatórias e hematopoéticas também tem sido demonstrada em animais e pacientes humanos (FIORETTI et al, 1998;HEVIN et al, 1990;SOIFFER et al, 1998 O processo inflamatório inclui liberação de citocinas, fatores de crescimento, polipeptídios quimiotáticos e prostaglandinas, os quais tornaram-se alvos favoritos para prevenção de cânceres de pele induzidos tanto por agentes químicos, quanto por radiação UV (MARKS e FURSTENBERGER, 2000;TRIPP et al, 2003;WILGUS et al, 2003;BOWDEN, 2004). Vários mediadores da inflamação apresentam papéis-chave na carcinogênese cutânea, como: as prostaglandinas, cicloxigenase-2, fator de necrose tumoral-α (TNF-α), AP-1, fator nuclear-κB (NF-κB), transdutor de sinal e ativador de transcrição (Stat) 3 e outros (BUCKMAN et al, 1998;MOORE et al, 1999;SUGANUMA et al, 1999;YOUNG et al, 1999;CHAN et al, 2004;LIND et al, 2004).…”
Section: A Inflamaçãounclassified